1974
DOI: 10.1002/ange.19740861608
|View full text |Cite
|
Sign up to set email alerts
|

Besseres Darstellungsverfahren für Mononatrium‐cyanamid

Abstract: matischen Vierkreisdiffraktometer (Hilger-Watts, Typ Y 290; MoK,-Strahlung; Graphit-Monochromator) geme~sen[~] [ Elementarzelle: a = 1047.9(4), b = 1302.2( l.l), c=754.5(5)pm; p =90.31(3)" 1.576(1) rad ; Raumgruppe C:,-P2,/n; Z = 4 ; d,"=6.31, dpgk=6.25gcm-3]. Die Strukturbestimmung mit 1 135 unabhangigen Reflexen fuhrte nach dreidimensionalen Fourier-Methoden zu einem vollstiindigen Strukturmodell (R-Wert 0.062 nach empirischer Absorptionskorrektur)I'l. Nach diesem Modell trifft die Hayeksche Formulierungl'l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…In a small volume pressure reactor were placed 20 milli-equiv. of a polyprimary amine (free base or hydrochloride salt), 3.08 g of 0-methylisouronium sulfate [23] and 10 ml of conc.…”
Section: Experimental Partmentioning
confidence: 99%
“…In a small volume pressure reactor were placed 20 milli-equiv. of a polyprimary amine (free base or hydrochloride salt), 3.08 g of 0-methylisouronium sulfate [23] and 10 ml of conc.…”
Section: Experimental Partmentioning
confidence: 99%
“…[12] 5-Bromosalicylaldehyde and sodium 5,5-diethylbarbiturate were purchased and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, very few dimethoxytriazines have been described [24][25][26][27][28][29][30][31][32][33][34], and some of their 2-(alk-1 0 -ynyl) derivatives such as I-III [35] present interesting cytotoxic activities toward different tumor cell lines (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The method utilized for the synthesis of these acetylenic compounds is the palladium catalyzed cross-coupling between alk-1-ynes and 2-chloro-4,6-dimethoxy-1,3,5-triazine [36][37][38]. As for their 2-alkyl analogs, they were often obtained by reacting zinc bis(imino-bismethyl carbamate) 3 with acid chloride or anhydride [25,26,33,34], and we have reported that 4 Å molecular sieves and pyridine can be advantageously utilized in this reaction [39,40]. The molecular structure of zinc salt was initially described as 3a [24], but we recently proved from an RX study (see 'Supporting information' section) that the real structure was 3b, 1 as suggested in a patent [25,26], but not confirmed (Fig.…”
Section: Introductionmentioning
confidence: 99%